VARIATIONS IN PARAMETRES OF PLATELET COUNT AND PLATELET VOLUME ACCORDING TO GESTATIONAL AGE - Akarsu, S.; Aydin, M.; Taskin, E. (Ferrata Storti Foundation, 2017)
[Abstract Not Available]
22nd Congress of the European-Hematology-Association -- JUN 22-25, 2017 -- Madrid, SPAIN